Analysis Of The Relevance Of Application Of Behavioristic Theory In The Development Of Positive Behavior In Early Childhood In The Era Of Information Technology - Ismaniar, Ismaniar; Utoyo, Setiyo; Septia Landa, Klara (KOLOKIUM Jurnal Pendidikan Luar Sekolah, 2023)
The era of information technology has a huge impact on human behavior, including in early childhood. The closeness that is quite intimate between children from an early age with various information technology equipment has brought various changes in children's behavior. Today's children tend to be more aggressive, lacking social and individual concern. Parents need to take this condition seriously so that it does not have a negative impact on the behavior and character of their children when they grow up. Behavioristic theory is a phenomenal theory and is one of the theories discovered and used by educational experts in developing and controlling human behavior. However, is this theory still relevant enough to be used in the development of children's behavior in this information technology era? The results of the analysis related to behavioristic theory and the characteristics of early childhood through various literature studies have concluded that behavioristic theory is still very suitable for use by parents in developing and controlling children's behavior today. So it is advisable for parents to continue to use behavioristic theory as a strategy in developing early childhood behavior.Keywords: Relevance,  Behavioristic Theory, Positive Behavior, Early Childhood,  The Era Of Information Technology